2006
DOI: 10.1029/2005tc001882
|View full text |Cite
|
Sign up to set email alerts
|

Counterclockwise rotation of late Eocene–Oligocene fore‐arc deposits in southern Peru and its significance for oroclinal bending in the central Andes

Abstract: The results of a paleomagnetic study along the fore arc of southern Peru (15–18°S) and northern Chile (18–19°S) are reported from middle to late Miocene ignimbrites (7 sites), late Oligocene to early Miocene ignimbrites (72 sites), Paleogene sediments (20 sites), and Mesozoic and Paleocene volcanics and intrusions (31 sites). Comparison of locality‐mean directions with expected paleomagnetic directions indicates vertical axis rotations ranging from 5.2 ± 11.3° clockwise to 55.6 ± 7.0° counterclockwise. Spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 95 publications
(174 reference statements)
5
124
0
1
Order By: Relevance
“…Subduction of the Nazca (and previously Farallon) Plate under the South American Plate has resulted in a mountain belt characterized by the largest trench‐to‐peak relief on the planet, frequent seismic activity ( M w  > 8.5), and a long‐standing history of volcanism (e.g., Armijo et al, 2015). Notably, three distinctly oriented sections of the range (Figure 1) may be the result of differential shortening recording periods of Andean deformation and uplift (Allmendinger et al, 1997; Isacks, 1988; Roperch et al, 2006), though this uniquely bent geometry may itself lead to focused deformation in the upper plate, particularly at plate corners (e.g., Bendick & Ehlers, 2014; Jordan et al, 1983). Other tectonic controls have been invoked to explain variation in Andean morphology (i.e., angle of convergence, convergence velocity, age of oceanic crust, and trench orientation), though no clear consensus exists on their relative importance (e.g., Barnes & Ehlers, 2009; Maloney et al, 2013; Oncken et al, 2006).…”
Section: Field Settingmentioning
confidence: 99%
“…Subduction of the Nazca (and previously Farallon) Plate under the South American Plate has resulted in a mountain belt characterized by the largest trench‐to‐peak relief on the planet, frequent seismic activity ( M w  > 8.5), and a long‐standing history of volcanism (e.g., Armijo et al, 2015). Notably, three distinctly oriented sections of the range (Figure 1) may be the result of differential shortening recording periods of Andean deformation and uplift (Allmendinger et al, 1997; Isacks, 1988; Roperch et al, 2006), though this uniquely bent geometry may itself lead to focused deformation in the upper plate, particularly at plate corners (e.g., Bendick & Ehlers, 2014; Jordan et al, 1983). Other tectonic controls have been invoked to explain variation in Andean morphology (i.e., angle of convergence, convergence velocity, age of oceanic crust, and trench orientation), though no clear consensus exists on their relative importance (e.g., Barnes & Ehlers, 2009; Maloney et al, 2013; Oncken et al, 2006).…”
Section: Field Settingmentioning
confidence: 99%
“…La discontinuidad cortical más relevante en la zona en estudio es sin duda el Sistema de Fallas de Atacama (SFA), que se dispone orientado paralelo a la fosa, y cuya geometría cretácica induce una importante herencia en la deformación actual. El registro paleomagnético de esta porción del oroclino no evidencia rotaciones mayores a 5º después del Mioceno (Arriagada et al, 2000;Coutand et al, 1999;Roperch et al, , 2006. La información geodésica del campo de deformación actual, indica que la mecánica de deformación del oroclino aun está activa (Allmendinger et al, 2005b), sin embargo no ha sido lo sufi cientemente efectiva después del Mioceno para producir deformación permanente que registre una rotación de bloques mayor a 5º.…”
Section: Síntesis Y Discusiónunclassified
“…This arrangement consists of (aparently) sinistral ~NW-SE wrench faulting that is interpreted to have facilitated uplift of the Coastal Cordillera (probably showing also sinistral behavior, i.e., IIIFS, as interpreted in Western Cordillera (Sempere and Jacay, 2006;Alván et al, 2015). A transtensive tectonic arrangement for southern Perú could be consistent with tectonic rotations as proposed Roperch et al (2006). Schildgen et al (2009), Decou et al (2013), Alván et al (2015) and Alván (2015) demonstrated that Western Cordillera in the study area experimented uplift with consequente denudation and deposition of sediments (Fig.…”
Section: The Origin Of Depocenters In Camaná-mollendo Basinmentioning
confidence: 52%
“…Fault scarps are mostly ~NW-SE oriented, and are visible along the sea floor up to the offshore of northern Chile (von Huene et al, 1996). If we prolongate alignments of the submarine canyons back to onshore, we observe that the thickest stackings of the Camaná Formation coincides with the river mouths of the large valleys at La Chira (16°30' S), Camaná (16°38' S), La Virgen (16°43' S), and Punta de Bombón (17°15' S) (Pecho and Morales, 1969;Sempere et al, 2004;Roperch et al, 2006).…”
Section: Morphology Of the Sea Flor In The Offshore Of Camanámentioning
confidence: 99%
See 1 more Smart Citation